2018
DOI: 10.5935/2595-0118.20180006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Pilates method on the treatment of chronic low back pain: a clinical, randomized, controlled study

Abstract: BACKGROUND AND OBJECTIVES: Low back pain is defined as a painful disorder located between the first and the fifth lumbar vertebra, and it is considered to be an important public health problem. In Brazil, approximately 10 million people are disabled as a result of this condition. The objective this study was to assess the effects of the Pilates method on the treatment of chronic low back pain. METHODS: The present study is based on a randomized, controlled clinical trial involving 16 individuals, aged 30-60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
0
14
0
6
Order By: Relevance
“…Taking into account that the painful perception and the presence of disabling conditions faced by individuals with CNLBP, such as fear-avoidance of pain [14], in addition to muscle weakness, especially in the deep abdomen muscles, and less articular flexibility in the spine and in the lower limbs [29,30], a possible interpretation to reduce pain and physical capacity limitations in the PG ranked as SBST Medium, is due to the fact that physical exercise is able to induce hypoalgesia, by activation of endogenous pain inhibitory systems [31]. In addition, the hypoalgesia exercise--induced improve general well-being, based on action on some psychological factors through multiple cellular and molecular events produced at different levels of the nervous system following physical exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account that the painful perception and the presence of disabling conditions faced by individuals with CNLBP, such as fear-avoidance of pain [14], in addition to muscle weakness, especially in the deep abdomen muscles, and less articular flexibility in the spine and in the lower limbs [29,30], a possible interpretation to reduce pain and physical capacity limitations in the PG ranked as SBST Medium, is due to the fact that physical exercise is able to induce hypoalgesia, by activation of endogenous pain inhibitory systems [31]. In addition, the hypoalgesia exercise--induced improve general well-being, based on action on some psychological factors through multiple cellular and molecular events produced at different levels of the nervous system following physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding exercises based on Pilates method, they can act with functional reeducation improving the overall posture and breathing pattern of these individuals, as well as strengthening the deep trunk muscles and the static and dynamic stability of the muscles related to the lumbar segment, favoring an improvement in health-related quality of life and a better performance in activities of daily and professional life [29,31]. Treatment with Pilates method still has variability in the length of service and sessions, but it is noteworthy that there is evidence [31] showing that the frequency of twice a week seems to be better than once a week and have similar effects to training three times a week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscular strength disorders are often found in patients with low back dysfunction, and it is estimated that > 80% of all cases of low back pain are caused by weakness of the trunk muscles. 19 Only Bhadauria et al assessed muscle strength by pressure biofeedback; as a result, they found no significant improvement in the Pilates group compared with the dynamic strengthening group and the stabilization group. Lower back, but showed significant improvement (p < 0.0001) within the Pilates group.…”
Section: Muscular Strength Range Of Movement and Flexibilitymentioning
confidence: 99%
“…Persistindo por mais de doze semanas, a lombalgia em níveis lombar e sacral é considerada crônica, ocasionando um desequilíbrio neuronal e hipersensibilidade a estímulos externos (Silva, et al, 2018). Já outros autores defendem que se deve esperar no mínimo seis meses para tal diagnóstico, pois existem fatores que alteram essa dor, como peso corporal, sedentarismo e excesso de sobrecarga em atividades laborais (Faria, 2013).…”
Section: Introductionunclassified